Analisis Kinerja Mekanik Bengkel Zicspeed Menggunakan Metode 360 Degree Feedback: Analysis of Mechanic Performance at Zicspeed Workshop Using the 360-Degree Feedback Method - Pratama, Kurniawan Adi; Hastasari, Ratih (CV Warnak Johanna Nusantara, 2025)
The automotive industry has grown rapidly as a key economic pillar, with workshops serving as vital components in the vehicle service ecosystem. ZicSpeed Workshop, as an automotive service provider, faces challenges in maintaining service quality standards amid increasing competition. This research aims to analyze mechanic performance at ZicSpeed Workshop using the 360 Degree Feedback method, focusing on comprehensive evaluation from various stakeholder perspectives. The research methodology adopts a descriptive quantitative approach, involving a sample of 10 mechanics consisting of 5 motorcycle mechanics and 5 car mechanics, with a research period from October to December 2024. Data collection was conducted through surveys, interviews, and literature studies, with assessment criteria including work quality, work speed, teamwork, customer satisfaction, and technical competence. The results show that car mechanics demonstrate higher performance in work quality (86%) compared to motorcycle mechanics (81.6%), while work speed for both divisions remains consistent at an average of 2.9 hours per job. Customer satisfaction and teamwork levels in the car division reached a score of 8.0, while the motorcycle division achieved 7.65. Technical competence in both divisions showed high standards with scores above 8.5. In conclusion, the implementation of the 360 Degree Feedback method proved effective in identifying workshop strengths and development areas, with recommendations for improving motorcycle division performance, work time optimization, evaluation system development, continuous professional development programs, and implementation of structured reward systems.